The Effect of Implementing Liveworksheets in Teaching Basic English Literacy - Pradnyadari, Ni Made Meita; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study investigates the impact of implementing Liveworksheets in teaching basic English literacy to tenth-grade students at a Senior High School in Bali. Literacy is a fundamental skill essential for educational success and daily life navigation. Indonesian students face unengaging reading content and language difficulties. This research addresses this issue by utilizing Liveworksheets, a digital platform that transforms traditional worksheets into interactive, multimedia-rich learning tools. This quasi-experimental study used a post-test-only control group design to determine whether there was a significant difference between the experimental and control groups in basic English literacy skills. Descriptive and inferential statistical analyses reveal that the experimental group outperformed the control group, with a mean score of 89.43 versus 74.49. The significance value obtained (p < 0.05) confirms the positive impact of Liveworksheets on students' literacy skills. Additionally, the effect size calculation indicates a substantial practical impact. The findings suggest integrating digital media like Liveworksheets into teaching practices can significantly improve student motivation, engagement, and learning outcomes. This study contributes to the theoretical understanding of digital media in education and offers practical insights for educators seeking innovative teaching tools to enhance literacy education.